Mevinolinic acid biosynthesis by Aspergillus terreus and its relationship to fatty acid biosynthesis. - Greenspan, M D (1985)
Mevinolinic acid, the open acid form of mevinolin, which is a metabolite of Aspergillus terreus, has been shown to be a competitive inhibitor of the enzyme 3-hydroxy-3-methylglutaryl coenzyme A reductase (Alberts et al., Proc. Natl. Acad. Sci. U.S.A. 77:3957-3961, 1980). The biosynthesis of mevinolinic acid was studied by examining the incorporation of [1-14C]acetate and [methyl-14C]methionine into the molecule. These isotopes were rapidly incorporated into mevinolinic acid, with [1-14C]acetate and [methyl-14C]methionine incorporation being linear for at least 10 and 30 min, respectively. A comparison of acetate incorporation into mevinolinic acid and fatty acids indicated that mevinolinic acid biosynthesis increased with a maximum between days 3 and 5 of growth; at this time cell growth had ceased and fatty acid biosynthesis was negligible. Hydrolysis of the mevinolinic acid and isolation of the products showed that [1-14C]acetate and [methyl-14C]methionine were incorporated into the 2-methylbutyric acid side chain as well as into the main (alcohol) portion of the molecule.